2016
DOI: 10.1136/jim-2015-000032
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Responses to Vitamin D3 (Cholecalciferol) in Patients on Dialysis: A Systematic Review and Meta-Analysis

Abstract: Vitamin D plays a key role in mineral metabolism and its deficiency is often noted in patients on dialysis for end-stage renal disease (ESRD). We evaluated the efficacy and responses to vitamin D3 (cholecalciferol) in patients undergoing dialysis for ESRD. Randomized controlled trials or prospective studies comparing vitamin D3 supplementation to placebo in patients with ESRD on dialysis were searched from medical databases using the terms, 'Calcitriol/Cholecalciferol, vitamin D, chronic kidney disease, hemodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 37 publications
0
6
1
Order By: Relevance
“…In subjects with SHPT due to vitamin D deficiency, supplementation with appropriate doses of calcifediol, cholecalciferol, or ergocalciferol was able to normalize the levels of 25(OH)D and PTH [74,75,76], although the evidence on the use of calcifediol was limited.…”
Section: Calcifediol In Different Clinical Settingsmentioning
confidence: 99%
“…In subjects with SHPT due to vitamin D deficiency, supplementation with appropriate doses of calcifediol, cholecalciferol, or ergocalciferol was able to normalize the levels of 25(OH)D and PTH [74,75,76], although the evidence on the use of calcifediol was limited.…”
Section: Calcifediol In Different Clinical Settingsmentioning
confidence: 99%
“…The BUN and creatinine are ideal for evaluation of renal function in renal diseases including ESRD [36]. The metabolism disorders in calcium and phosphorus are considered as a major contributor to UP in dialysis patients [37]. The excessive retention of PTH and β2-MG may paly important role in pruritus, peripheral nerve changes, vascular calcification and renal osteodystrophy in patients with ESRD [38].…”
Section: Discussionmentioning
confidence: 99%
“…( 20 , 21 ) Consistently, most RCTs conducted among patients on dialysis failed to demonstrate a beneficial effect of vitamin D supplementation on PTH levels. ( 9 , 10 , 22 , 23 , 24 ) Meanwhile, Taniguchi and colleagues demonstrated that successful KTx causes regression of the parathyroid gland with diffuse hyperplasia and restores its expression of VDR. ( 12 ) Probable VDR restoration and high 25(OH)D levels, coupled with accelerated conversion of 25(OH)D to 1,25(OH) 2 D due to secondary hyperparathyroidism and healthy kidney transplanted, could contribute to PTH reduction by cholecalciferol supplementation in the current study.…”
Section: Discussionmentioning
confidence: 99%